THE CRUCIAL SHIELD: WHY VACCINATION IS PARAMOUNT? - Akhmatov Bokhodirjon Khalimjon ugli; Axmadjonov Umrbek Axrorjon ugli (Western European Studies, 2024)
Few medical interventions compete with vaccines for their cumulative impact on health and well-being of entire populations. Routine immunization of children in the United States now targets 16 vaccine preventable diseases; and vaccines are now routinely given across the lifespan. Immunization efforts achieved the global eradication of smallpox, as well as the elimination of polio, measles, and rubella from the Americas. The childhood vaccine series including DTP, polio, MMR, Hib, hepatitis B, and varicella vaccines is estimated to prevent 14 million infections, avoid 33,000 premature deaths, and save $9.9 billion in direct costs as well as $33 billion in indirect costs for each U.S. birth cohort fully vaccinated. Newer vaccines such as pneumococcal conjugate, rotavirus, and hepatitis A vaccines have also reduced illness and hospitalizations among the target populations but also have amplified benefits beyond their direct effects through reduced transmission from those immunized toother groups. Although for most of the 20th century there was a substantial delay between a vaccine’s introduction in developed countries and its broad use in poor countries, newer global public–private partnerships and advocacy are leading to accelerated uptake of new and underutilized vaccines. Since the Measles Initiative was established in 2001, more than 700 million children worldwide have received a measles vaccination and an estimated 4.3 million childhood measles deaths have been averted. The full impact of increasing routine immunization further and implementing new vaccines against.(6,7)
Keywords: vaccine; immunization; epidemiology